2023
DOI: 10.1007/s43390-023-00746-2
|View full text |Cite
|
Sign up to set email alerts
|

The Dutch version of the Spinal Appearance Questionnaire for adolescents with idiopathic scoliosis: patient-based cross-cultural adaptation and measurement properties evaluation

Dineke G. van de Fliert,
Tom P. C. Schlösser,
Diederik H. R. Kempen
et al.

Abstract: Purpose Adolescent idiopathic scoliosis (AIS) affects the appearance of spine and trunk. The Spinal Appearance Questionnaire (SAQ) assesses the perception of appearance in AIS patients. The aim of this study is to translate and culturally adapt the recommended short version of the SAQ into Dutch and to test its measurement properties. Methods A Dutch SAQ (14-item; appearance and expectations domains) was developed following guidelines for translation and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
0
0
0
Order By: Relevance
“…√ √ √ √ √ √ A 5-item questionnaire, consisting of 5 dimensions (mobility, self-care, usual activities, pain/discomfort, and anxiety/depression) QALYs will be estimated using the Dutch tariff [25] Condition-specific quality of life (PROM): SRS-22r -Dutch version [26] √ √ √ √ √ √ A 22-item questionnaire, consisting of 5 domains (pain [5 items], self-image [5 items], function ([5 items], mental health [5 items], and satisfaction with management [2 items]) and a total score, with scores ranging 1 to 5 for each item Pain (PROM) Numerical Rating Scale (NRS) √ √ √ √ √ √ Ranging from 0 (no pain) to 10 (worst imaginable pain) for mean pain since last visit Spinal appearance questionnaire (PROM): Short SAQ √ √ √ √ √ √ A 14-item questionnaire [27,28], consisting of a total score and 2 domain scales, "appearance" (10 items) and "expectations" (4 items), with scores ranging from 1 to 5 Global Perceived Effect (PROM): GPE √ √ √ √ √ √ 2 items ranging in score from 1 to 7 regarding satisfaction with the treatment effect [29] Education status (PROM) Patient-reported √ √ √ √ √ √ Absence from school, absence from physical education (PE) classes, frequency of missing school exams, necessity to repeat a class, support and alternatives provided by the school Health-related and societal costs (PROM): Questionnaires √ √ √ √ √ √ Costs will be collected with cost questionnaires (modified iPCQc , iMCQ, and iViCQ). Resource use will be valued in accordance with the Dutch Manual for Costing Studies in Health Care [30] Angle of trunk rotation (ATR, °; patient-reported) Scolioscope (only PE-FU) √ √ √ √ √ √ The asymmetry of the spine results in an ATR and a rib hump, which will be measured by the parent/caregiver Curve progression (ATR, °; clinician-reported) The Bunnell scoliometer [11] √ √ √ √ √ √ Patient-reported questions after surgery (post-surgery group only): Return to school, return to sport √ √ -√ -√ Radiographic assessment (full spineradiograph; clinician-reported) √ √ √ √ √ √ Progression of deformity in the primary and compensatory Cobb angels (°).…”
Section: Study Follow-up and Data Collectionmentioning
confidence: 99%
“…√ √ √ √ √ √ A 5-item questionnaire, consisting of 5 dimensions (mobility, self-care, usual activities, pain/discomfort, and anxiety/depression) QALYs will be estimated using the Dutch tariff [25] Condition-specific quality of life (PROM): SRS-22r -Dutch version [26] √ √ √ √ √ √ A 22-item questionnaire, consisting of 5 domains (pain [5 items], self-image [5 items], function ([5 items], mental health [5 items], and satisfaction with management [2 items]) and a total score, with scores ranging 1 to 5 for each item Pain (PROM) Numerical Rating Scale (NRS) √ √ √ √ √ √ Ranging from 0 (no pain) to 10 (worst imaginable pain) for mean pain since last visit Spinal appearance questionnaire (PROM): Short SAQ √ √ √ √ √ √ A 14-item questionnaire [27,28], consisting of a total score and 2 domain scales, "appearance" (10 items) and "expectations" (4 items), with scores ranging from 1 to 5 Global Perceived Effect (PROM): GPE √ √ √ √ √ √ 2 items ranging in score from 1 to 7 regarding satisfaction with the treatment effect [29] Education status (PROM) Patient-reported √ √ √ √ √ √ Absence from school, absence from physical education (PE) classes, frequency of missing school exams, necessity to repeat a class, support and alternatives provided by the school Health-related and societal costs (PROM): Questionnaires √ √ √ √ √ √ Costs will be collected with cost questionnaires (modified iPCQc , iMCQ, and iViCQ). Resource use will be valued in accordance with the Dutch Manual for Costing Studies in Health Care [30] Angle of trunk rotation (ATR, °; patient-reported) Scolioscope (only PE-FU) √ √ √ √ √ √ The asymmetry of the spine results in an ATR and a rib hump, which will be measured by the parent/caregiver Curve progression (ATR, °; clinician-reported) The Bunnell scoliometer [11] √ √ √ √ √ √ Patient-reported questions after surgery (post-surgery group only): Return to school, return to sport √ √ -√ -√ Radiographic assessment (full spineradiograph; clinician-reported) √ √ √ √ √ √ Progression of deformity in the primary and compensatory Cobb angels (°).…”
Section: Study Follow-up and Data Collectionmentioning
confidence: 99%